2019
DOI: 10.1104/pp.19.00489
|View full text |Cite
|
Sign up to set email alerts
|

GATA and Phytochrome Interacting Factor Transcription Factors Regulate Light-Induced Vindoline Biosynthesis in Catharanthus roseus

Abstract: Catharanthus roseus is the exclusive source of an array of terpenoid indole alkaloids including the anticancer drugs vincristine and vinblastine, derived from the coupling of catharanthine and vindoline. Leaf-synthesized vindoline is regulated by light. A sevenstep enzymatic process is involved in the sequential conversion of tabersonine to vindoline; however, the regulatory mechanism controlling the expression of genes encoding these enzymes has not been elucidated. Here, we identified CrGATA1, an Leu-Leu-Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 84 publications
3
72
0
Order By: Relevance
“…Metabolic engineering is an efficient approach for improving the production of active ingredients in medicinal plants. This process requires a deep understanding of the biosynthesis pathways of active ingredients, including both biosynthesis-related and regulatory genes 22 25 . Although great progress has been made in the isolation and functional identification of biosynthesis-related genes involved in medicinal compounds, little is known about the transcriptional regulation of phenolic acid biosynthesis in S. miltiorrhiza .…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic engineering is an efficient approach for improving the production of active ingredients in medicinal plants. This process requires a deep understanding of the biosynthesis pathways of active ingredients, including both biosynthesis-related and regulatory genes 22 25 . Although great progress has been made in the isolation and functional identification of biosynthesis-related genes involved in medicinal compounds, little is known about the transcriptional regulation of phenolic acid biosynthesis in S. miltiorrhiza .…”
Section: Introductionmentioning
confidence: 99%
“…A crucial regulatory mechanism in specialized metabolism is the transcriptional regulation of biosynthetic genes. Several transcription factors (TFs) involved in MIA regulation have been identified in Catharanthus , including the octadecanoid‐responsive Catharanthus AP2‐domain (ORCA) TF family and the zinc finger Catharanthus (ZCT) TF family described below (Menke et al, ; Van der Fits & Memelink, ; Van der Fits, Zhang, Menke, Deneka, & Memelink, ; Sibéril et al, ; Chatel et al, ; Pauw et al, ; Vom Endt, Soares e Silva, Kijne, Pasquali, & Memelink, ; Zhang et al, ; Suttipanta et al, ; Van Moerkercke et al, , ; Paul et al, ; Liu et al, ; Liu, Patra, Pattanaik, Wang, & Yuan, ; Patra, Pattanaik, Schluttenhofer, & Yuan, ; Pan et al, ). Three characterized members ( ZCT1 , ZCT2, and ZCT3 ) of the Cys 2 /His 2 ‐type (C 2 H 2 ) zinc finger family are expressed by the stress‐induced phytohormone jasmonate (Goklany, Rizvi, Loring, Cram, & Lee‐Parsons, ; Pauw et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…But both overexpressing and silencing CrERF5 had limited effect on vindoline accumulation, indicating that CrERF5 might not control vindoline pathway. It has been reported that light-induced vindoline biosynthesis is regulated by GATA and PIF transcription factors in C. roseus (Liu et al, 2019). But the genes in the steps from strictosidine to vinblastine, like STR1, Redox1, SAT , and CrPRX1 , were upregulated in CrERF5-overexpressing petals and downregulated in CrERF5-silencing plants, leading to a significant increase of the catharanthine, anhydrovinblastine and vinblastine accumulation.…”
Section: Discussionmentioning
confidence: 99%